Object oriented programming through Java - Radha Krishna, P. (Universities Press (India) Private Limited, 2007)
Covering both the fundamentals and applications, this book offers an introduction to Java. It includes coverage of essential topics such as classes, objects, packages, interfaces, multi threading, AWT, Applets, and Swings